Analysis of algorithms of interference coding and improving the efficiency in the complex systems - Oleg Pavlovich Malofey; Alexander Olegovych Malofey; Anastasia Evgenievna Shangina (Наука. Инновации. Технологии, 2022)
When creating new technical solutions it is necessary to ensure the technical parameters which set cost is the lowest. It is advisable to use the principle of minimum costs and restrictions on the technical effect, as well as the external and internal parameters that characterize the information protection system errors. The methodological basis for solving optimization problems is also the theory of operations research. Since the system is created to protect information from error, providing the required noise immunity value of the indicator Psmp at minimum cost Cmp, the performance indicator of permissible projects may be instrumental in the creation of processing costs reliability of the device У1. The problem of optimal mathematical programming is reduced to finding the number of repetitions of the function argument values of the message m and the likelihood of distortion of a single character codeword P0, which minimize the functional, and can be solved by a classical method of Lagrange multipliers.